(untitled) (Research, Society and Development, 2023)
Acquired syphilis is one of the most worrying sexually transmitted infections in Brazil, as it exhibits several stages and can cause from tissue lesions to dementia and vascular damage, it does not always present clinical manifestations, even asymptomatic a person can transmit and disseminate the infection, making it a difficult epidemiology control. The objective of this research is to analyze the spatial distribution of individuals affected by syphilis acquired in the North region of Brazil in the period 2019-2022, promoting strategies for actions and control of the disease, considering the factors that interfere with access to treatment. The research carried out is of a descriptive, retrospective, clinical and epidemiological nature through an study of the analyzes of the information system of notifiable disease (Sinan Net). The results indicate that during the analysis period, 39,884 cases of syphilis were notified in the North region of Brazil alone, where the state of Amazonas (37%), Pará (25%) and Rondônia (12%) lead the list of notifications followed by states with lowest notifications, Tocantins (10%), Acre (6%), Amapá (5%) and Roraima (5%). The male gender continues to be the most affected, since the age group 20 to 29 for both genders has been the most recurrent for more than a decade, suggesting that sex education, protection, prevention and more efficient treatment plans be drawn up for this public.